Найти производные функций: а) y= (x^3 - 2)*(x^2 + x +1); б) y=(x + 2)*(2x^3 - x); в) y=(x^2 + 1)*(x^3 - x); г) ( x^3 - 1)*(x^2 + x); д) y=(x^4 - 3)*(x^2 + 2); е) y=( x^2 - 1 |x^2 +1 )

2

Ответы и объяснения

2011-12-06T10:38:32+04:00

(x^3-2)*(x^2+x+1)'=3x^2*(x^2+x+1)+(x^3-2)*(2x+1)

(x+2)*(2x^3-x)'=(2x^3-x)+(x+2)*(6x^2-1)

x^2+1)*(x^3-X)'=2x(x^3-x)+(x^2+1)(3x^2-1)

г)= 3x^2*(x^2+x)+(x^3-1)(2x+1)

д)= 4x^3*(x^2+2)+(x^4-3)2x 

 

2011-12-06T17:17:07+04:00

а)

\\y= (x^3 - 2)(x^2 + x +1)\\ y'=3x^2(x^2+x+1)+(x^3-2)(2x+1)\\ y'=3x^4+3x^3+3x^2+2x^4+x^3-4x-2\\ y'=5x^4+4x^3+3x^2-4x-2\\

 

б)

\\y=(x + 2)(2x^3 - x)\\ y'=2x^3-x+(x+2)(6x^2-1)\\ y'=2x^3-x+6x^3-x+12x^2-2\\ y'=8x^3+12x^2-2x-2\\

 

в)

\\y=(x^2 + 1)(x^3 - x)\\ y'=2x(x^3-x)+(x^2+1)(3x^2-1)\\ y'=2x^4-2x^2+3x^4-x^2+3x^2-1\\ y'=5x^4-1

 

г)

\\y=( x^3 - 1)(x^2 + x)\\ y'=3x^2(x^2+x)+(x^3-1)(2x+1)\\ y'=3x^4+3x^3+2x^4+x^3-2x-1\\ y'=5x^4+4x^3-2x-1

 

д)

\\y=(x^4 - 3)(x^2 + 2)\\ y'=4x^3(x^2+2)+(x^4-3)\cdot2x\\ y'=4x^5+8x^3+2x^5-6x\\ y'=6x^5+8x^3-6x\\

 

е)

это неразборчивый